Uganda Economic Update, 17th Edition, June 2021 : From Crisis to Green Resilient Growth – Investing in Sustainable Land Management and Climate Smart Agriculture - World Bank (World Bank, Washington, DC, 2021)
The Ugandan economy is recovering from a sharp contraction due to the COVID-19 (coronavirus) shock that had slowed growth to its lowest pace in over three decades. Real GDP growth is estimated to reach above 3 percent during FY21, following the modest recovery of 0.7 percent in the first half of the FY. On a calendar year basis, real GDP had contracted by 1.1 percent in 2020, due to the almost total lockdown that lasted over four months, border closures except for essential cargo, and the spillover effects of the disruption in global demand on Ugandan exports, remittances and foreign direct investments. The services sector was particularly hard hit, contracting by over 3 percent in 2020, with activities in key sectors like education and accommodation and food services largely curtailed for most of the year. As restrictions were loosened, business and trading conditions improved both locally and globally allowing investments to pick up in the last quarter of 2020, with stronger signs of recovery in the manufacturing and construction sectors continuing into the quarter ending March 2021. Growth in agriculture has been sustained through the cash crops sector, which is relatively better than the food crop sector, in the use of improved farming practices to manage weather variability.